Implementasi Layanan Konseling Individual untuk Meningkatkan Interaksi Sosial Siswa Berkepribadian Introvert di Sekolah Dasar - Setia Hasanah Zuhdi (Insan Cendekia : Jurnal Pendidikan dan Kebudayaan, 2024)
Student learning activeness is one of the key indicators of successful classroom instruction, particularly in mathematics learning, which often presents challenges for elementary school students. This study aimed to improve the learning activeness of third-grade students through the implementation of interactive PowerPoint media based on a tutorial approach in learning the properties of plane figures. The research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, consisting of planning, action, observation, and reflection. The study was conducted at SDN Pakong 5 involving five third-grade students. Data were collected through observation, interviews, and questionnaires, and were analyzed descriptively using percentage analysis. The findings revealed that the implementation of interactive PowerPoint media successfully increased students' learning activeness. The average percentage of learning activeness reached 80%, categorized as very active, with each indicator exceeding the predetermined success criterion of 75%. In addition, the teacher's instructional performance achieved a score of 3.54, which falls into the good category. These findings indicate that interactive PowerPoint media based on a tutorial approach can create a more engaging learning environment, encourage active student participation, and improve learning activeness in mathematics lessons at the elementary school level.